The Postglacial Vegetation History in Southwestern Bulgaria. A Paleoecological Approach - Tonkov, Spasimir (Advanced Books, 2021)
This book presents the results from the palynological and paleoecological studies conducted with my participation in Southwestern Bulgaria during the period 1985-2020. The study area has always played a key role in the investigation of the Late Quaternary vegetation history in Bulgaria since the middle of the past century. With the development of the research methods (pollen analysis, determination of plant macrofossils, radiocarbon dating, sediment analysis, computer software, etc.) in the last decades it turned out to be a challenge for me to evaluate critically again and synthesize the paleoecological information. In my opinion, such an approach allows us to reveal in more details the general trends of the postglacial vegetation development for the last 18000-15000 years and to take also into account the role of humans in transforming the natural environment after the establishment of agriculture and the practice of stockbreeding in this part of the country along the Struma river.